Hey, not sure if this is even a good website to pose this question, but I thought I'd try it out.

I'm trying to teach myself some programming language principles by going through various texts/problem sets I find online about lambda calculus. Haven't gotten too far and I'm still trying to work the whole thing out. One statement I'm confused by is this:

If we assume λy.λx.x = λy.λx.yx then we can say that any two lambda terms are equal.

I'm sort of scratching my head on why this is true. Any explanations or leading statements would be much appreciated.

Thanks!